Analisa Perbandingan Rumus Haversine Dan Rumus Euclidean Berbasis Sistem Informasi Geografis Menggunakan Metode Independent Sample t-Test - Retno Palupi; Diyan Ayuk Yulianna; SM Santi Winarsih (JITU : Journal Informatic Technology And Communication, 2021)
Comparative Analysis of the Haversine Formula and the Euclidean Formula based on Geographical Information Systems which aims to analyze and compare the measurement results of the two formulas whether there are significant differences to the distance measured based on geographic information systems. Research objects used to collect distance data are several bank offices in the city of Solo. The method used in this research is to create a geographic information system application using web-based programming using the PHP (Pearl Hypertext Prepocessor) programming language, with the MySQL database. Measurements were carried out on two formulas, namely the Haversine formula and the Euclidean formula and obtained data in the form of distances in kilometers (km) which were obtained from the program system, then the data was processed using Statistical Product and Service Solution (SPSS) 23 software. is the Independent Sample t-test method. From the data analysis, the conclusion is that there is no significant difference in the calculation of the distance between the Haversine formula and the Euclidean formula. The Independent Sample T Test method is able to analyze the comparison of distance measurements using the Haversine formula and the Euclidean formula does not have a significant difference, meaning that the variants of the two formulas are the same. Kata Kunci : Haversine formula, Euclidean formula , geographic information system, Independent Sample t-Test Method